2014
DOI: 10.1021/pr401251k
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Saccharomyces cerevisiae Lysine Methylation: Insights into Non-histone Protein Lysine Methyltransferase Activity

Abstract: Post-translational lysine methylation is well established as a regulator of histone activity; however, it is emerging that these modifications are also likely to play extensive roles outside of the histone code. Here we obtain new insights into non-histone lysine methylation and protein lysine methyltransferase (PKMT) activity by elucidating absolute stoichiometries of lysine methylation, using mass spectrometry and absolute quantification (AQUA), in wild-type and 5 PKMT gene deletion strains of Saccharomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The differences in stoichiometry of the methylation sites, which ranges from ϳ85% for the N-terminal methylation to between 2.5 and 13% for other sites (50), is also suggestive of this. However, the stoichiometry observed here for the N-terminal methylation should be confirmed by a more accurate measurement, such as absolute quantification, to allow a direct comparison with previous studies (50). It is likely that all methylation sites can co-occur, as previous whole protein mass spectrometric analysis found that eEF1A exists at an average mass roughly equal to what is expected for all lysine methylation sites plus N-terminal acetylation (17), now known to be N-terminal trimethylation.…”
Section: Methyltransferases That Act On Lysine 79 In Eef1a Arementioning
confidence: 88%
See 1 more Smart Citation
“…The differences in stoichiometry of the methylation sites, which ranges from ϳ85% for the N-terminal methylation to between 2.5 and 13% for other sites (50), is also suggestive of this. However, the stoichiometry observed here for the N-terminal methylation should be confirmed by a more accurate measurement, such as absolute quantification, to allow a direct comparison with previous studies (50). It is likely that all methylation sites can co-occur, as previous whole protein mass spectrometric analysis found that eEF1A exists at an average mass roughly equal to what is expected for all lysine methylation sites plus N-terminal acetylation (17), now known to be N-terminal trimethylation.…”
Section: Methyltransferases That Act On Lysine 79 In Eef1a Arementioning
confidence: 88%
“…While the exact function of their resulting methylation sites is unknown, the fact that they act upon one protein suggests they may modulate various functions of eEF1A (16). The differences in stoichiometry of the methylation sites, which ranges from ϳ85% for the N-terminal methylation to between 2.5 and 13% for other sites (50), is also suggestive of this. However, the stoichiometry observed here for the N-terminal methylation should be confirmed by a more accurate measurement, such as absolute quantification, to allow a direct comparison with previous studies (50).…”
Section: Methyltransferases That Act On Lysine 79 In Eef1a Arementioning
confidence: 99%
“…Gel lanes were excised into 28 slices according to protein mass, which were destained (when required), reduced, and alkylated following standard procedures (29). In-gel tryptic digestions and peptide extractions were performed following procedures described previously (30). Peptide extraction solutions were dried in a SpeedVac TM and reconstituted in 20 l of 0.1% (v/v) formic acid.…”
Section: Methodsmentioning
confidence: 99%
“…This methylpeptide identifies arginine methylation on a known protein-arginine methyltransferase substrate motif, RGG (6,8,18,34), further supporting the designation of this match as a true positive. In addition, three methylpeptides designated as true positives identified two alternative forms of lysine methylation on known elongation factor 1-␣ methylation sites: di-methylation on Lys-390 (previously only characterized as MML) and tri-methylation on Lys-316 (previously only characterized as MML and DML) (30,37). XIC and synthetic peptide-derived MS/MS data used to validate these methyl-PSMs are presented in supplemental Figs.…”
Section: Fig 1 Workflows Employed In the Investigation Of Methyl-psmentioning
confidence: 99%
See 1 more Smart Citation